Max Kade Institute Friends Newsletter, Vol. 7, no. 3, Fall 1998 - Lind, Michael; Langer, Edward G.; Devitt, Mary; Salmons, Joseph; Karolle, K. Julia; Geiger, Steven R. (My University, 1998)
Contents: "'Defining Tensions' Conference Schedule" --- "Lectures, at the MKI and Statewide" --- "Crossing New Boundaries: 'Concepts of Regionalism'" --- "Frank P. Gross in Memoriam" --- "German Playgroup Started" --- "Electronic List" --- "Landskroner Emigration to the Midwest" --- "Fall German Classes."
Keywords: Midwest; Conferences; Austrian Americans; Immigration Studies; German Americans--Emigration and immigration--History--19th century